Analysis Of Consumer Buying Interest In Food Products In The Shopee Application - Sri Lestari, Yayuk Endang; Efriyani Sumastuti; Henry Casandra Gultom (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of this study is to investigate the impact of Shopee’s pricing points, promotions, product ratings, and transactional convenience on customers’ propensity to purchase food items. A quantitative approach is used in this study. Shopee users come from all throughout Indonesia, therefore this demographic is representative of the country’s variety and spread. A convenience sample of 110 participants was used for this research. The data analysis methods used in this research include multiple linear regression on primary data. This study found that while price and sales promotions did not affect purchasing interest, product rating did, and ease of transactions did as well. What’s more, purchasing interest was influenced by discounts, prices, promotions, product ratings, and ease of transactions all at once.